Socio-Economic Impact of Agropolitan Area Development Among Chrysanthemum Farmer - Lia, Reza Siskana; Satmoko, Sriroso; Prayoga, Kadhung (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
Chrysanthemum farmers had encountered significant issues during the agropolitan program implementation. Their small-scale business, seasonal fluctuation, poor knowledge and innovation contribute as hindrances in running the program. This study aimed to explore the socio-economic impact of the agropolitan program among the farmer. We conducted a study in December 2019 on the Gemah Ripah Farmer Group. Purposive sampling technique was applied to recruit thirty-four farmers from the farmer group as study participants. This was a descriptive study with a qualitative approach. Literature review, interview sessions, and observation were conducted to collect the study data. Data analysis consisted of three steps: 1) data reduction, 2) data display, and 3) conclusion and verification. The data validity was tested by credibility, transferability, dependability, and confirmability test. Results revealed that the social impact percieved by the farmer was the ease in accessing daily needs and health care, intimate relationship between farmer and local people, development and refinement of cropping tools, and stronger institutional structure of the farmer group. The economic impact observed were improvement of the narrow field utility value, income enhancement, and improvement of employment opportunities. Further studies are required to explore more perspectives to obtain varied information from a different layer of parties involved in the programs.